Ab initio identified design principles of solid-solution strengthening in Al - Duancheng Ma, Martin Friák, Johann von Pezold, Dierk Raabe and Jörg Neugebauer (Science and Technology of Advanced Materials, 2013)
Solid-solution strengthening in six Al–X binary systems is investigated using first-principle methods. The volumetric mismatch parameter and the solubility enthalpy per solute were calculated. We derive three rules for designing solid-solution strengthened alloys: (i) the solubility enthalpy per solute is related to the volumetric mismatch by a power law; (ii) for each annealing temperature, there exists an optimal solute–volume mismatch to achieve maximum strength; and (iii) the strengthening potential of high volumetric mismatch solutes is severely limited by their low solubility. Our results thus show that the thermodynamic properties of the system (here Al–X alloys) set clear upper bounds to the achievable strengthening effects owing to the reduced solubility with increasing volume mismatch.